Impacts of extreme climate events on Brazilian agricultural production - Carvalho, André Luiz de; Santos, Diogo Victor; Marengo, José Antônio; Coutinho, Sonia Maria Viggiani; Maia, Stoécio Malta Ferreira (Sustainability in Debate, 2020)
Brazilian agricultural production stands out in world food security, accounting for a large part of the food produced worldwide. However, occurrence of extreme climate events is a challenge for the sector across the country. Thus, this study aims to assess extreme climate events impacts on Brazilian agricultural production. The loss index was calculated using crop data made available by the IBGE from 2005 to 2017, while data on the occurrence of extreme climate events (2002-2017) was obtained from literature. Data related to PROAGRO (2010-2018) and the Crop Assurance Program (2002-2016) were obtained from reports made available by the relevant agencies. Results showed high drought-induced production losses, mainly maize and beans produced in the Caatinga biome, and soybean and wheat in the Southeastern and Southern regions of the country. Hail and frost events also caused reductions in soybean and rice production in the Southeastern and Southern regions. Those impacts on the Brazilian agricultural production, in different regions, might have serious consequences on the availability and access of food to the population in the country.